SINKRONISASI HARGA SAHAM MELALUI KUALITAS AKRUAL DAN RISIKO PASAR DI BURSA EFEK INDONESIA STUDI KHASUS PERUSAHAAN PERBANKAN - Dedi Putra; Putri Azhura (Jurnal Akuntansi dan Keuangan, 2019)
The objectiveof this researchwas examining empirically the correlation between the nondiscretionary accruals, the discretionary accrual and the market  risk on the stock price synchronization. The non discretionary sccruals, the discretionary accruals and the market risk were regarded as the specific information of companies. The subject of this research was tge specific information of companies. The subject of this research was the banking companies indexed in Indonesia Stock Exchange in the period of 201-2017. The result of this research showed that the nondiscretionary accruals affected the stock price synchronicity, the discretionary accrual did not affect the stock price synchronicity and the market risk did noot affect the stock price synchronicity. The important of this research was that the nondiscretionary accruals were the important factor for the investors to decide the specific infrormation of companies for the decision making of the capital market.